The Risky Business of Migration: Interdisciplinary Approaches to Decision Making and Risk in the Study of Migration - OʼReilly, William (Dějiny – teorie – kritika, 2021)
This article reviews the research strategies employed by historians, economists, political scientists, and others when assessing human movement both at present and in the past. Migration systems are replete with long-established migration paths as well as anomalous events. Yet historians regularly fail to engage with questions of motivation for migration, how migrants reach a decision on when and where to go, how agents and agencies of migration aid or inhibit efforts to relocate, and how risk is a significant factor in decision making regarding migration. This article critically reviews a range of approaches from other disciplines and assesses the value for historians of considering a range of theories concerning risk and risk management in assessing how migrants in the past – and today – make the decision to uproot. This study is a contribution to the historiography of migration studies and calls for historians to approach the history of human movement in a more interdisciplinary way. Keywords: historiography of migration studies, migration risks, interdisciplinary migration history, decision making.